Chota Motala. The Making of a South African Political Biography. (3rd April 2019) - Vahed, Goolam
ABSTRACT: Drawing on my experience of writing an account of Chota Motala, a Pietermaritzburg-based medical doctor and anti-apartheid activist, this article considers some of the historiographical and methodological challenges of writing biography in general, and South African political biographies in particular. On a general level, this includes whether biography is 'inferior' history, an 'illusion', and whether it can be written in a linear manner. Specific to my study, this article considers the theoretical and contextual issues relating to South African political biography; the role of the sources in shaping the narrative; the subjective process of writing a biography; and the variance in interpreting the character of Motala and his contribution in the political sphere.